Quantum capacitance in strained armchair Graphene nanoribbon considering Edge effect - Mondol, Raktim Kumar; Hassan, Asif S.; Hasan, Rifat (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 1st IEEE International Conference on Electrical, Computer and Communication Technologies, ICECCT 2015; SVS College of EngineeringCoimbatore; India; 5 March 2015 through 7 March 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICECCT.2015.7225950